Model of Strengthening The Constitutional Rights of The Community Through Village Fund Supervisory Groups as An Effort to Prevent Corruption - Nurita, Riski Febria; Nahuddin , Yusuf Eko; Sabrina, Nahdiya (International Journal of Accounting and Economics Studies, 2025)
This research discusses the management of Village Funds in Indonesia, focusing on the challenges of misuse that lead to criminal acts of corruption. Village Funds, allocated at Rp71 trillion for the 2025 fiscal year, are intended to support the development and empowerment of village communities. However, corruption practices in the management of Village Funds remain a major issue that harms the state and society. The research method used in this study is the normative juridical research method, which emphasizes the study of existing legal norms, both in legislation and relevant legal principles. One of the proposed solutions is the strengthening of the constitutional rights of village communities through the establishment of Village Fund Supervisory Groups (KPPD), aimed at increasing community participation in the oversight, transparency, and accountability of Village Fund management. In addition, this study promotes the application of principles of good governance, such as transparency, accountability, participation, and the rule of law as the normative foundation to ensure that the allocation and use of Village Funds are oriented toward public welfare and free from abuse. This research uses a normative juridical approach to analyze regulations governing Village Funds, the constitutional rights of village communities, and the principles of good governance as the basis for oversight and management. The goal of this study is to propose a model for strengthening the supervision of Village Funds through the Village Fund Supervisory Groups (KPPD), and to provide policy recommendations aimed at reducing corruption and improving the welfare of village communities.